Apakah Persepsi Harga dan Cita Rasa Berpengaruh terhadap Keputusan Pembelian Ayam Geprek Rocket Chicken - Munawaroh Munawaroh; Septiyanitha Dwi Maharani Putri; Rayhan Gunaningrat (Jurnal Publikasi Ilmu Manajemen, 2024)
This research aims to determine the role of price and taste perceptions on purchasing decisions for rocket fried chicken. The variables used in this research are price and taste perceptions as independent variables, purchasing decisions as the dependent variable. The data collection technique used in this research is data from questionnaire answers distributed to respondents on a Likert scale with the highest value being 5 and the lowest being 1. The data analysis technique used in this research uses Smart (PLS) Partial Least Squares. The population in this research is the number of consumers purchasing Geprek Chicken for Students of the Faculty of Law and Business, Duta Bangsa Angakatan University, Surakarta in 2020, namely 358 students as consumers. The sample used in this research was 71.6 respondents. The research results show that price perceptions have a positive influence on purchasing decisions and taste has a positive influence on purchasing decisions.